2015 IEEE 13th International Conference on Industrial Informatics (INDIN) 2015
DOI: 10.1109/indin.2015.7281840
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-compression based iterative time-of-flight extraction of dispersed Ultrasonic Guided Waves

Abstract: Ultrasonic Guided Wave (UGW) based Non-Destructive Testing (NDT) systems are widely used in numerous branches of industry, where the structural integrity of components carries vital importance. In those systems, signal interpretations might become challenging due to multi-modal and dispersive response of the structure under examination. This results in degradation of the signals in terms of Signalto-Noise Ratio (SNR) and spatial/temporal resolution. This paper uses Maximal Length Sequences (MLS) to develop a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…No information about the accuracy of the method detecting ToA of the different wave-packet was produced. Yucel et al [16], [17] integrated both aforementioned techniques in a brute-force search algorithm, and then compared the performance of Maximal Length Sequence (MLS) and chirp excitation waveforms in terms of ToA accuracy and SNR enhancement. Their results proved the ability of the method to detect accurate ToA for flexural wave modes in multimodal and superposed scenarios.…”
Section: Wave Mode Discrimination Of Coded Ultrasonicmentioning
confidence: 99%
See 1 more Smart Citation
“…No information about the accuracy of the method detecting ToA of the different wave-packet was produced. Yucel et al [16], [17] integrated both aforementioned techniques in a brute-force search algorithm, and then compared the performance of Maximal Length Sequence (MLS) and chirp excitation waveforms in terms of ToA accuracy and SNR enhancement. Their results proved the ability of the method to detect accurate ToA for flexural wave modes in multimodal and superposed scenarios.…”
Section: Wave Mode Discrimination Of Coded Ultrasonicmentioning
confidence: 99%
“…With this technique, the specific propagation distance travelled by the wave-packet is necessary. Yucel et al [16] implemented this as part of an exhaustive search algorithm that compensated the signals for a range of propagation distance values before the application of the cross-correlation. Once the signals were compensated for a specific distance and cross-correlated, the peak value of the signal was acquired.…”
Section: Proposed Technique and Implementationmentioning
confidence: 99%
“…In 2010, they published another paper using the same system where the phase modulation based on Golay codes were used where the enhancement of 21 dB in SNR using a 16-bit Golay code was achieved compared to the conventional pulse transmission. Mehmet et al [10,11], introduced an iterative dispersion compensation for removing the dispersion effect of guided-wave propagation. Most recently, Malo et al [12] developed a two-dimensional compressed pulse analysis in order to enhance the achieved SNR of each wave mode.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Zeng et al [8] used the basis of the dispersion compensation technique and introduced a novel method to design waveforms in order to pre-compensate for a certain propagation distance. Various researchers investigated the pulse compression approach, which consisted of exciting a known coded sequence and match-filtering the results in order to detect the known sequence [9][10][11][12]. Mehmet et al [9,10] introduced an iterative dispersion compensation for removing the dispersion effect of guided-wave propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers investigated the pulse compression approach, which consisted of exciting a known coded sequence and match-filtering the results in order to detect the known sequence [9][10][11][12]. Mehmet et al [9,10] introduced an iterative dispersion compensation for removing the dispersion effect of guided-wave propagation. In 2016, Lin et al [11] reported on the performance of different excitation sequences in terms of their ability to achieve δ-like correlation on Lamb waves.…”
Section: Introductionmentioning
confidence: 99%